Patients' satisfaction as a dimension of quality: a survey on outpatients' care in Dubai. Issue 8 (8th October 2018) - Mahboub, Bassam; Mawasi, Ahmad; Ali, Souzan; Spina, Chiara
Abstract : Purpose: The last few years have seen a stronger emphasis on patient-centred care within the international healthcare setting. Patient-centred care is clearly perceived to be important to optimise the satisfaction and well-being of patients. The purpose of this paper is to review current patient-centred practices for outpatients in both private clinics and public hospitals in Dubai. Such a comparison contributes to the identification of best management practices as a means of enhancing healthcare delivery. Design/methodology/approach: This study is based on an independent survey consisting of self-administered questionnaires, in which patients were asked to rate several aspects of private clinics or government hospitals in Dubai. The questionnaire used has been drawn from the Consumer Assessment of Healthcare Providers and Systems Clinician and Group Survey, Version 3.0. Responses from 420 patients form a data set that is analysed quantitatively. Findings: In total, 420 respondents took part in this survey. The results of the survey show that there is a considerable difference between the expectation levels of patients from government hospitals and patients from private clinics. Patients from government hospitals consistently show that time is a critical aspect of the service received, with 68 per cent of the respondents reporting this issue. Additionally, poor customer care, as reported by 14 per cent of the respondents, is also a critical issue. Timely service and appointments are among the main factors that contribute to patient satisfaction. Patients in private clinics, instead, particularly value clear explanations from doctors and nurses – this is corroborated by the fact that 11 per cent of the respondents reported appreciation of this type of service. Practical implications: This paper draws attention to a patient-centric perspective of healthcare, and highlights the importance of educating patients through clear explanations. Originality/value: Little evidence exists on the standards of healthcare in Dubai. The authors explore this area and present direct evidence on quality standard implementation, identify implementation shortcomings and make recommendations for future research and practice.